Effect of application of potassium fertilizer on the growth and yield of tomatoes at different salinity levels - Nurul Aini; Wiwin Sumiya Dwi Yamika; Wendy Dwi Andrian; Elok Sukmarani (Journal of Degraded and Mining Lands Management, 2019)
Tomatoes are a horticultural commodity and the main priority to be developed in Indonesia. To improve the production of tomatoes, land expansion is needed. Managing marginal land to grow tomatoes can be an option. Marginal land such as saline land has the potential to be developed as an alternative. This research is aimed to investigate the effect of K fertilizer on the growth and yield of tomato plants at different levels of salinity. The experiment was conducted in a greenhouse located in the rural area of Bendosari in Kediri, East Java, using factorial randomized block design. The first factor was NaCl concentration (0, 3000, 6000 and 9000 ppm) while the second factor was the dosage of ZK fertilizer (75, 150 and 225 kg/ha). The results Showed that salinity level reduced growth and yield of tomato while the dosage of ZK fertilizer did not affect. Salinity level on 3000 ppm reduced leaf area 20.35 %, shoot dry weight 27.18%, root dry weight 28 %, number of fruit 24.14 %, fruit weight per fruit 29.82 % and fruit weight per plant 12.42 %. However, salinity level on 6000 and 9000 ppm ware not significantly different at all variables except 6000 ppm in leaf area (reduced 37.06%) and 9000 ppm on the number of fruit (reduced 43.01%).